Decreased Hospitalizations and Costs From Infection in Sixteen Nursing Homes in the SHIELD OC Regional Decolonization Initiative. (October 2020) - Gussin, Gabrielle M.; McKinnell, James A.; Singh, Raveena D.; Kleinman, Ken; Miller, Amherst Loren; Saavedra, Raheeb; Heim, Lauren; Estevez, Marlene; Catuna, Tabitha D.; Lee, Eunjung; Tjoa, Thomas; Slayton, Rachel; et al.
Abstract : Distinguished Oral Background: Shared Healthcare Intervention to Eliminate Life-threatening Dissemination of MDROs in Orange County, California (SHIELD OC) was a CDC-funded regional decolonization intervention from April 2017 through July 2019 involving 38 hospitals, nursing homes (NHs), and long-term acute-care hospitals (LTACHs) to reduce MDROs. Decolonization in NH and LTACHs consisted of universal antiseptic bathing with chlorhexidine (CHG) for routine bathing and showering plus nasal iodophor decolonization (Monday through Friday, twice daily every other week). Hospitals used universal CHG in ICUs and provided daily CHG and nasal iodophor to patients in contact precautions. We sought to evaluate whether decolonization reduced hospitalization and associated healthcare costs due to infections among residents of NHs participating in SHIELD compared to nonparticipating NHs. Methods: Medicaid insurer data covering NH residents in Orange County were used to calculate hospitalization rates due to a primary diagnosis of infection (counts per member quarter), hospital bed days/member-quarter, and expenditures/member quarter from the fourth quarter of 2015 to the second quarter of 2019. We used a time-series design and a segmented regression analysis to evaluate changes attributable to the SHIELD OC intervention among participating and nonparticipating NHs. Results: Across the SHIELD OC intervention period, intervention NHs experienced a 44% decrease in hospitalization rates, a 43% decrease in hospital bed days, and a 53% decrease in Medicaid expenditures when comparing the last quarter of the intervention to the baseline period (Fig. 1). These data translated to a significant downward slope, with a reduction of 4% per quarter in hospital admissions due to infection ( P < .001), a reduction of 7% per quarter in hospitalization days due to infection ( P < .001), and a reduction of 9% per quarter in Medicaid expenditures ( P = .019) per NH resident. Conclusions: The universal CHG bathing and nasal decolonization intervention adopted by NHs in the SHIELD OC collaborative resulted in large, meaningful reductions in hospitalization events, hospitalization days, and healthcare expenditures among Medicaid-insured NH residents. The findings led CalOptima, the Medicaid provider in Orange County, California, to launch an NH incentive program that provides dedicated training and covers the cost of CHG and nasal iodophor for OC NHs that enroll. Funding: None Disclosures: Gabrielle M. Gussin, University of California, Irvine, Stryker (Sage Products): Conducting studies in which contributed antiseptic product is provided to participating hospitals and nursing homes. Clorox: Conducting studies in which contributed antiseptic product is provided to participating hospitals and nursing homes. Medline: Conducting studies in which contributed antiseptic product is provided to participating hospitals and nursing homes. Xttrium: Conducting studies in which contributed antiseptic product is provided to participating hospitals and nursing homes.